Global burden of diphtheria, 1990–2021: a 204-country analysis of socioeconomic inequality based on SDI and DTP3 vaccination differences before and after the COVID-19 pandemic (GBD 2021) - Zilun Wu; Zilun Wu; Liyu Lin; Liyu Lin; Jinbu Zhang; Jinbu Zhang; Jirui Zhong; Jirui Zhong; Donglan Lai; Donglan Lai; Donglan Lai (Frontiers in Public Health)
ObjectiveThis study aimed to comprehensively assess the temporal trends and regional disparities in the global burden of diphtheria across 204 countries and territories from 1990 to 2021, as well as evaluate the impact of vaccination coverage on disease transmission.MethodsData were extracted from the Global Burden of Disease (GBD) 2021 study. Statistical approaches, including Joinpoint regression, nonlinear fitting, and calculation of the average annual percentage change (AAPC), were employed to analyze diphtheria incidence, mortality, and disability-adjusted life years (DALYs). The Pearson correlation coefficient was used to quantify the association between diphtheria-tetanus-pertussis (DTP3) vaccination coverage and incidence. Analyses were stratified by region, sex, age, and socio-demographic index (SDI).ResultsBetween 1990 and 2021, the global age-standardized incidence rate (ASIR), mortality rate (ASMR), and DALY rate (ASMR) of diphtheria declined by 86.7, 75.0, and 86.4%, respectively, yet marked regional disparities persisted. Higher SDI levels correlated with reduced burden, with low-SDI regions accounting for 88.4% of global DALYs in 2021, while high-SDI regions approached elimination. DTP3 coverage negatively correlated with incidence (r = −0.191, p = 0.011), suggesting vaccination may reduce disease burden. We further analyzed confounders like SDI, drug resistance, health systems, surveillance gaps, and economic development. During the COVID-19 pandemic, global DTP3 coverage declined from 86 to 81%. Despite continued reductions in incidence—potentially linked to respiratory protective measures and historical immunization buffering—post-pandemic vaccination programs must be prioritized to mitigate resurgence risks, particularly in low-SDI and endemic regions.ConclusionOver the past three decades, global efforts have significantly reduced the diphtheria burden, but systemic challenges remain in low-SDI regions. Vaccination remains pivotal; however, post-pandemic declines in coverage underscore latent epidemic risks. Low-SDI regions require integrated nutrition-vaccination strategies, conflict-adapted delivery, and robust cold chains, while high-SDI areas should enhance genomic surveillance, adult boosters, and equitable technology sharing. This study provides the first systematic quantification of spatiotemporal diphtheria burden patterns, offering critical evidence for the WHO 2030 Diphtheria Elimination Roadmap. Eliminating regional disparities necessitates strengthened healthcare systems and adult booster immunization strategies.